The Form Analysis of Bekir Sıdkı Sezgin The Muhayyer Sümbüle Mevlevî Âyîn-i Şerîf - AKARSU, Sitki (Zenodo, 2023)
The term Ayin is used in the history of religions, Sufism and Turkish religious music. It is of Persian origin and carries the meanings of ceremony, procedure, style of worship, customs and traditions. It also expresses various musical ceremonies and worship styles belonging to different religions in some sects. Collective ceremonies have turned into a certain ritual and include bodily movements as well as prayers and works read aloud within the rules adopted by the community. It has manifested itself since the earliest times of mankind that the bodily movement and vocal expression in this ceremonial atmosphere in the rituals. He shaped the contents of the rites that all social causes and mystical elements in human life such as birth, death, seasonal periods, protection from disasters. In fact, it has been ensured that there is an order and continuity in the practices due to the function attributed to the rites by the political structures. The use of the concept of ritual in Islamic geography depends on its occurrence in religious sources. However, when we look at its spread, Persian has had an influence on mystical practices in terms of culture(Başoğlu, 2020: 367). The origin of the word Ayin is based on Persian and the Turks used this word exactly. But Arabs preferred words that have the same meaning like "Hadran, Hafle, Urs"(Tıraşçı, 2020: 20). This word which is widely used in Turkish culture was mostly used in Mevlevi ceremonies in the field of Turkish music. These types of music composed are called “Âyin-i Şerif”. The biggest religious form of Turkish music is the "rite" form (Macit, 2021). Mevlevis do it with the intention of worship apart from the prayer, we also perform the ritual of turning called Sema accompanied by the Âyin-i Şerif. (In the real sky, the dervish says and remembers Allah at every turn. Zikr-i Hafi. This too is worship (Tosun, 2020).) The works were composed by great musicians which the works performed during the "Sema". It is also difficult to compose these works, which are in a special classification in terms of shape. The Mevlevi sect has been instrumental in raising important names in music through rituals with this difficult aspect. The old Mevlevi lodges can also be considered as the first Turkish conservatories outside the palace (Özkan, 1998: 82). In this study, it is aimed to determine the formal features of "Muhayyer Sümbüle Âyin-i Şerif", whose composition belongs to Bekir Sıdkı Sezgin. It is intended to be detected the musical aspect of the work and the structure of motifs, sentences and chapters. It is thought that this study will serve to field studies on classical Turkish music. Method In the study was used descriptive survey model, which is one of the qualitative research methods. Scanning model is a descriptive model as it exists a situation that exists in the past or present. It is a research approach that tries to define the event, individual or object that is the subject of research in its own conditions and as it is (Karasar, 2005: 77). Universe and Sample The universe of the study consists of all the Mevlevi Ayins that have been composed until today. The sample is composed of the lyrical note of Muhayyer Sümbüle Âyin-i Şerif composed by composer Bekir Sıdkı Sezgin and related sources made about the field. Data Collection and Analysis The notes of Muhayyer Sümbüle Ayîn'i Şerif, which will be analyzed first were obtained from the web environment during the data collection phase(www.mutrıban.com). The measures in the note are numbered for convenience. In addition, vertical lines were used in the note in order to increase the clarity of the measures in the musical sentences. Findings and Comments In total 251 measures were used in 4 parts of the work. There are 46 measures in the 1st Chapter (1st Selam); In the 2nd part (2.Selam) 22 measures; 175 measures in Section 3(3.Selam) and 8 measures in Section 4(4.Selam). There are 8 musical sentences in the 1st Selam, 3 musical sentences in the 2nd Selam, 19 musical sentences in the 3rd Selam, and 2 musical sentences in the 4th Selam. There are 32 musical phrases in total. Conclusion and Recommendations "Âyin-i Şerifs" have been the products of composers who are generally affiliated with that group, due to being a Mevlevi tradition, form of worship and ritual. It is difficult and unwelcome that trying to write the Mevlevi ritual without knowing that community. But is rare the writing of such comprehensive and high-level works in today. There are 167 Ayin-i sharifs used in ritual ceremonies. Maybe it meets the demand. Therefore, although the composition of such important works makes incredible contributions to the field of Turkish music, a work to be done for the composition of the rites, competence and competence points should not be overlooked in every step to be taken.

{"references": ["Arel, H. S. (1954). Mevlevi Musikisi ve Ayinleri. Musiki mecmuas\u0131, 73, 3-6.", "Bayrak\u00e7\u0131, \u00d6. F. (2015). T\u00fcrk Din M\u00fbsik\u00eesi'nde \"Mevlev\u00ee Ayini\" Formuna Genel Bir Bak\u0131\u015f. Eski\u015fehir Osmangazi \u00dcniversitesi \u0130lahiyat Fak\u00fcltesi Dergisi, 2, 139-152.", "\u00c7\u0131pan, M ve Karaman, S. (2010). Dede Efendi'nin Y\u00fcr\u00fck Sem\u00e2\u00eelerinin Us\u00fbl-Ar\u00fbz Vezni \u0130li\u015fkisi Y\u00f6n\u00fcnden \u0130ncelenmesi. T\u00fcrkiyat Ara\u015ft\u0131rmalar\u0131 Dergisi, 28, 485-522.", "\u00c7\u0131rak, C. (2021). S\u00e2dullah A\u011fa'n\u0131n Zenc\u00eer Bestelerinde \u00dcsl\u00fbp ve Mak\u00e2m\u0131n Bi\u00e7ime Etkisi. EJMD, (18), 106-173.", "\u00c7oban, \u015e. (2021). Bekir S\u0131dk\u0131 Sezgin'in Hayat\u0131, Sanat\u0131 ve Eserleri. Bal\u0131kesir \u0130lahiyat Dergisi, 14, 211-250.", "\u0130rden, S. (2011). Dede Efendi'nin Sab\u00e2 \u00c2y\u00een-\u00ee \u015eer\u00eef\u00ee'nin Makam, Ge\u00e7ki, \u00c7e\u015fni Analizi. T\u00fcrkiyat Ara\u015ft\u0131rmalar\u0131 Dergisi, 30, 553-600.", "\u0130rden, S. (2012). Hamm\u00e2m\u00eez\u00e2de \u0130sm\u00e2il Dede Efendi'nin Mevlev\u00ee \u00c2y\u00eenlerindeki Makam ve Form Anlay\u0131\u015f\u0131n\u0131n T\u00fcrk Din M\u00fbsik\u00eesine Etkileri. \u0130dil Dergisi, 1(4), 60-83.", "Ka\u00e7ar, G. Y. ve Desteg\u00fcl, A. (2021). Cinu\u00e7en Tanr\u0131korur'a Ait K\u00e2r\u00e7e-i N\u00fch Felek Eserinin Bi\u00e7im \u00d6zellikleri A\u00e7\u0131s\u0131ndan Tahl\u00eeli. \u0130stem, 18(36), 253-282.", "Ka\u00e7ar, G. Y. (2013). Hatip Z\u00e2kir\u00ee Hasan Efendi'nin N\u00fch\u00fcft Makam\u0131ndaki \u0130mam H\u00fcseyin Mersiyesi. T\u00fcrk K\u00fclt\u00fcr\u00fc ve Hac\u0131 Bekta\u015f Vel\u00ee Ara\u015ft\u0131rma Dergisi, 66, 239-254.", "Ka\u00e7ar ve Yurdag\u00fcl, (2021). Mustafa C\u00e2zim el-Mevlev\u00ee'ye \u00c2it Hicazk\u00e2r Mevlev\u00ee \u00c2y\u00een-i \u015eer\u00eefi'nin Bi\u00e7im Y\u00f6n\u00fcnden Tahl\u00eeli, NE\u00dc Press-\u0130stem, 19/37 (2021): 1-28.", "Macit, M. (2021). T\u00fcrk m\u00fbsiki tarihinde Mevlevi musikisinin yeri, \u00f6nemi ve etki alan\u0131 hakk\u0131nda genel bir de\u011ferlendirme. Balkan M\u00fczik ve Sanat Dergisi, 3(1), 37-54."]}
Keywords: Semantic Versioning 2.0.0